Iowa Birdline update, February 27, 1989 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1989)
Notes for the Iowa Birdline update for February 27, 1989. Highlights include Trumpeter and Tundra Swans, Glaucous and Thayer's Gulls, and a roosting Prairie Falcon. Epson - sheet feed/flatbed